FENOMENA MONDAY EFFECT PADA INDEKS HARGA SAHAM GABUNGAN INDONESIA - Eliza Noviriani; Soraya Soraya; Zulham Al Farizi (Jurnal Akuntansi Indonesia, 2018)
The purpose of this research is to get empirical evidence about Monday effect phenomenon on Indonesia Composite Stock Price Index. The diversity of arguments and research results on the Monday effect phenomenon derived from previous studies makes this phenomenon interesting to investigate. By using Kruskal Wallis test and Simple Regression on 246 daily stock returns during 2016, it can be concluded that there is no Monday effect phenomenon on Indonesia Composite Stock Price Index. It causes condition of Indonesia capital market in 2016. Results show the average positive return occurs in almost all trading days. Only returns on Friday show negative values. This condition shows that the year was a year with a good investment climate so that the frequency of stock trading tends to be positive and evenly throughout the year. In addition, the absence of the Monday effect phenomenon is also marked by the absence of the effect of stock return Friday the previous week against stock returns Monday. These results indicate that form of a weak market efficiency. That means the past data is unrelated to the present value of the Indonesian capital market in 2016.